2000
DOI: 10.1577/1548-8659(2000)129<0982:huabco>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Utilization and Biological Characteristics of Adult Atlantic Sturgeon in Two South Carolina Rivers

Abstract: Thirty‐nine adult Atlantic sturgeon Acipenser oxyrinchus oxyrinchus (136–234 cm total length) were caught in gill nets fished at historical sturgeon‐fishing locations in the Combahee and Edisto rivers (South Carolina) during spring and fall 1998. All fish were tagged (with passive integrated transponders and darts), and radio and acoustic transmitters were surgically implanted in 29 fish. When possible, gonad biopsies were taken for sex and maturity‐stage determination. Locations of telemetered fish were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 23 publications
5
61
2
Order By: Relevance
“…Generally it is thought that juvenile Atlantic Sturgeon stay in riverine areas year-round, while adults move into rivers during spring for spawning but move out into marine environments during other times (Smith 1985;Bain 1997). Our study and others (Moser and Ross 1995;Collins et al 2000) have observed adult and subadult Atlantic Sturgeon in riverine areas during summer. In an ongoing study in the Roanoke RiverAlbemarle Sound system, most sonic-tagged adult Atlantic Sturgeon were present during the summer months (two of three in 2011, five of five in 2012, and three of six in 2013), not in offshore marine waters (authors' unpublished data).…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Generally it is thought that juvenile Atlantic Sturgeon stay in riverine areas year-round, while adults move into rivers during spring for spawning but move out into marine environments during other times (Smith 1985;Bain 1997). Our study and others (Moser and Ross 1995;Collins et al 2000) have observed adult and subadult Atlantic Sturgeon in riverine areas during summer. In an ongoing study in the Roanoke RiverAlbemarle Sound system, most sonic-tagged adult Atlantic Sturgeon were present during the summer months (two of three in 2011, five of five in 2012, and three of six in 2013), not in offshore marine waters (authors' unpublished data).…”
Section: Discussionsupporting
confidence: 62%
“…This zone, the freshwater-saltwater interface, probably contained most of a river's available Atlantic Sturgeon encompassing 1 m, although side-scan detections of sturgeon sometimes occurred to the upper extent of survey reaches (Flowers and Hightower 2013, Supplement A). We did not observe sturgeon in our surveyed portion of the Santee River, resulting in a 0 population estimate, but sturgeon have been observed there in the past (Collins et al 2000). A different survey design would be required to produce estimates that would apply to each entire river.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations